2013
DOI: 10.1111/ics.12084
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled clinical trial to investigate the effect of Cynatine®HNS on skin characteristics

Abstract: Cynatine(®) HNS is an effective supplement for improving skin in 90 days or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Clinical trials also demonstrated that Cynatine R FLX1 (Beer et al, 2013b) and Cynatine R HNS (500 mg/day; Roxlor LLC, Delaware, USA; Beer et al, 2014) could supplement bioactive peptides and amino acids responsible for protecting and rebuilding damaged joints and improving the growth and strength of hair and nails. Other product claims include boosting body protein supply and promoting healing on injury or vigorous activity (Beer et al, 2013a(Beer et al, , 2014Kelly et al, 2007;. Wool-derived keratin hydrogels can accelerate wound healing by stimulating tissue regeneration (i.e., new capillaries and collagen synthesis) and hair follicle development (Moore et al, 2016).…”
Section: Keratin Peptides As Bioactive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials also demonstrated that Cynatine R FLX1 (Beer et al, 2013b) and Cynatine R HNS (500 mg/day; Roxlor LLC, Delaware, USA; Beer et al, 2014) could supplement bioactive peptides and amino acids responsible for protecting and rebuilding damaged joints and improving the growth and strength of hair and nails. Other product claims include boosting body protein supply and promoting healing on injury or vigorous activity (Beer et al, 2013a(Beer et al, , 2014Kelly et al, 2007;. Wool-derived keratin hydrogels can accelerate wound healing by stimulating tissue regeneration (i.e., new capillaries and collagen synthesis) and hair follicle development (Moore et al, 2016).…”
Section: Keratin Peptides As Bioactive Agentsmentioning
confidence: 99%
“…Another study showed improvement in skin and nail health in a randomized 90‐day administration of Cynatine® (500 mg keratin/day) to 50 females ( n = 25 per group) compared with a placebo control group ( n = 25; Beer et al., 2013a). The oral ingestion of keratin tablets showed improved skin hydration, elasticity, wrinkle reduction and increased compactness.…”
Section: Benefits Of Dietary Keratinmentioning
confidence: 99%